Utilization of Plant Based Attractants in Labeo rohita Advanced Fingerlings Diet - Singh, P; Mahintamani, J.; Maity, J. (Indian Journal of Animal Nutrition, 2020)
Feed attractants are the substances which are added in trace amount in a diet to enhance the overall palatability and dry matter intake of feed. A 30 day experiment was conducted to study the efficacy of plant based attractants in the feed of Labeo rohita advanced fingerlings (average weight 17.0±0.05 g) and 10 fingerlings were stocked in duplicate for each dietary treatment. The initial body weight of the fish of each group was non-significant (P>0.05). The diet was formulated with rice bran, mustard oil cake, fish meal, vitamin and mineral mixture, binder along with 1% of different feed attractants and different feeds were named as F1 (Control), F2 (Ekangi, Kaempferia galanga), F3 (Kharboj, Cucumis melo) and F4 (Marigold, Tagetes patula). The net weight gain were 2.53±0.23, 4.16±0.15, 5.50±0.4 and 2.41±0.35 (g/30 days) respectively in F1 to F4. The water quality such as dissolved oxygen, pH and temperature ranged from 5.5-6.5 mg/l, 7.2-7.4 and 30.50-32.00C respectively during the experimental period in treatment groups. The growth study with different attractants revealed that the final weight, net weight gain, specific growth rate, daily growth co-efficient was significantly (P<0.05) higher in F3 having 1% kharboj. However, Feed conversion ratio was (P>0.05) lower in F3 having kharboj as feed attractants. Thus, from the present experiment it may be concluded that F3 having 1% kharboj performed better in terms of growth performance and feed intake in Labeo rohita advanced fingerlings vis-à-vis other feed treatments.